2017
DOI: 10.1080/10410236.2017.1323320
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia in the News: The Role of News Frames in Shaping Online Reader Dialogue about Mental Illness

Abstract: A quantitative content analysis examined the portrayal of schizophrenia in eight of the most read online news publications in the United States. The analysis documented the prevalence of stigma frames, which communicate stereotypes concerning schizophrenia, and stigma-challenge frames, which contradict stereotypes, in 558 articles related to schizophrenia. The study also examined the relationship between media framing and reader commentary, including the likelihood of readers posting stigmatizing comments, sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
17

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 28 publications
2
30
0
17
Order By: Relevance
“…Results of the three studies comparing the impact of reading positive, neutral or negative published news reports consistently showed that positive reports that challenged stigma, were informative and focused on recovery, were likely to lead to reductions in stigmatising attitudes, while negative reports that included stereotypes of violence and dangerousness increased stigmatising attitudes [24,32,33]. Further, in an analysis of comments on online news reports, reports that communicated positive information about mental illness were more likely to attract comments of support and stigma-challenging comments from readers, while reports that associated mental illness with violent behavior and quoted people with a mental illness were accompanied by a greater proportion of stigmatising comments [33].…”
Section: Impact Of News Reports On Stigmamentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the three studies comparing the impact of reading positive, neutral or negative published news reports consistently showed that positive reports that challenged stigma, were informative and focused on recovery, were likely to lead to reductions in stigmatising attitudes, while negative reports that included stereotypes of violence and dangerousness increased stigmatising attitudes [24,32,33]. Further, in an analysis of comments on online news reports, reports that communicated positive information about mental illness were more likely to attract comments of support and stigma-challenging comments from readers, while reports that associated mental illness with violent behavior and quoted people with a mental illness were accompanied by a greater proportion of stigmatising comments [33].…”
Section: Impact Of News Reports On Stigmamentioning
confidence: 99%
“…Of the seven studies investigating the impact of news media, three investigated the impact of positive versus negative portrayals in news reports [24,32,33], two explored the influence of news reports of shootings carried out by a person with a mental illness [34,35], and two investigated the impact of retrospectively recalled news reports on mental illness [36,37]. Of the three experimental studies [24,32,35], two were assessed as having strong methodological quality, while the other was assessed as being weak in quality.…”
Section: Impact Of News Reports On Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars probing the relationship between media framing and reader commentary revealed that media consumers are more likely to disclose their personal experiences when the media coverage is framed in a way that challenges stigmatization. (e.g., Gwarjanski & Parrott, 2018). However, the glaring hole exhibited in the extant literature is that extremely limited studies have investigated whether the levels in which a story is told have an impact on the reactions among its consumers.…”
Section: Levels Of Storytellingmentioning
confidence: 99%
“…The evidence suggests that community attitudes to mental illness are appreciably influenced by the cumulative effect of this media exposure (see Pirkis & Francis, , for a review). This negative depiction is particularly true of schizophrenia, where both entertainment (Owen, ) and news media (Clement & Foster, ; Gwarjanski & Parrott, ) frequently associate the condition with violent incidents.…”
Section: Introductionmentioning
confidence: 99%